KAJIAN LITERATUR IMPLEMENTASI BUILDING INFORMATION MODELING (BIM) DI INDONESIA - Januar Pantiga; Anton Soekiman (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2021)
One of the most common obstacles encountered in the construction industry is the fragmented delivery process and relies on paper-based documentation and communication. To overcome these problems a good integration system is needed. Building Information Modeling (BIM) is a construction technology innovation that can help stakeholders to collaborate, visualize, and manage construction work better. However, the adoption rate of BIM in Indonesia is still behind compared to other countries. This research was conducted to gather information about the BIM adoption experience and the challenges and benefits faced by construction actors in Indonesia. This study uses the literature review method for data collection. Based on the results of the study it was found that in general the level of adoption of BIM by construction actors in Indonesia is still low, the main challenge faced is the high investment costs of BIM applications, while time efficiency is the dominant benefit of using BIM.